Recent Advances in Particulate Matter and Nanoparticle Toxicology: A Review of the In Vivo and In Vitro Studies. (19th June 2013) - Nemmar, Abderrahim; Holme, Jørn A.; Rosas, Irma; Schwarze, Per E.; Alfaro-Moreno, Ernesto
Abstract : Epidemiological and clinical studies have linked exposure to particulate matter (PM) to adverse health effects, which may be registered as increased mortality and morbidity from various cardiopulmonary diseases. Despite the evidence relating PM to health effects, the physiological, cellular, and molecular mechanisms causing such effects are still not fully characterized. Two main approaches are used to elucidate the mechanisms of toxicity. One is the use of in vivo experimental models, where various effects of PM on respiratory, cardiovascular, and nervous systems can be evaluated. To more closely examine the molecular and cellular mechanisms behind the different physiological effects, the use of various in vitro models has proven to be valuable. In the present review, we discuss the current advances on the toxicology of particulate matter and nanoparticles based on these techniques.